What hearing children think regarding the inclusion of deaf children in the regular classroom: a comparative study with Brazilian children in a public and a private school - Beatriz Vargas Dorneles; Virginia Bedin; Isabel Cristina Peregrina Vasconcelos; Rosane da Conceição Vargas (Universidade Federal de Santa Maria (UFSM), 2010)
The present study investigates how hearing children relate to the presence of a deaf child in a classroom group. An analysis is made of the influence of social class in relation to the acceptance of the deaf child by the hearing children. The 144 children from the 3rd to 5th series that participated in the study were distributed thus: 76 from a private school and 68 from a public school, both from Porto Alegre, RS. The public school largely attended lower level socioeconomic classes, while the private school attended pupils from predominantly middle to upper social classes. All received the same task: Complete a story that describes the reaction of hearing students to the insertion of a new deaf colleague in the classroom group. The study demonstrates that pupils wish to attempt to communicate with the deaf child and would socialize with the child outside the classroom. They demonstrate a somewhat protective discourse in relation to the subject who they consider disabled but not incapable of communicating. Understanding how hearing children relate to, and include a deaf child within the classroom, raises the possibility of new forms of thinking regarding the preparation of hearing children to possible inclusion processes. Recognizing their ideas, feelings and forms of communication aids educational institutions to invest in inclusion policies.